2021
DOI: 10.1111/jocs.16118
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of concomitant ablation for atrial fibrillation in rheumatic mitral valve surgery: A meta‐analysis

Abstract: Objectives: This review aimed to evaluate the safety and efficacy of concomitant surgical ablation (SA) for patients with atrial fibrillation (AF) undergoing rheumatic mitral valve (MV) surgery.Methods: A systematic search of relevant studies focusing on SA for patients with AF undergoing rheumatic MV surgery was performed. The primary outcomes included mortality, efficacy, and complications.Results: Four randomized controlled trials (RCTs) and four observational studies covering 1931 patients met the inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In addition to increasing the risk of mortality, it also causes socioeconomic problems by causing morbid consequences such as heart failure and stroke. 1 47.6%, specificity: 77.6%). 3…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In addition to increasing the risk of mortality, it also causes socioeconomic problems by causing morbid consequences such as heart failure and stroke. 1 47.6%, specificity: 77.6%). 3…”
mentioning
confidence: 89%
“…Atrial fibrillation (AF) is the most common arrhythmia with a prevalence ranging from 2% to 4% in the adult population. In addition to increasing the risk of mortality, it also causes socioeconomic problems by causing morbid consequences such as heart failure and stroke 1 . Postoperative atrial fibrillation (PoAF) is a frequent complication ranging from 10% to 60% after major surgical interventions (cardiac surgery, pulmonary thromboendarterectomy [PTE], aortic surgery, etc.)…”
mentioning
confidence: 99%
“…Concomitant SA during rheumatic MV surgery does not increase perioperative adverse events more effective in sinus rhythm restoration than MV surgery alone at discharge and 1- and 3-year follow-up. 52 Surgical AF ablation has a class IIa recommendation in patients with valvular heart disease undergoing surgery in the recent AF guidelines. 4 …”
Section: Rhythm Control In Rheumatic Afmentioning
confidence: 99%
“…10 Similarly, some studies concluded that the additional surgical ablation also decreased the risk of stroke or death and increased early and long-term sinus rhythm maintenance in patients with AF and RMVD. [11][12][13] However, there has been debate on the standard surgical ablation strategy during MV operations. Generally, bi-atrial (BA) lesion set could be created during surgical ablation because the open left atrium facilitates a BA ablation procedure, nevertheless, others believed that adding right atrial ablation had no influence on freedom from AF and conversely increased the risk of permanent pacemaker implantation.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Gillinov et al reported the addition of surgical ablation to MV surgery significantly increased the rate of freedom from AF at 1 year among patients with persistent or long-standing persistent AF in a multicentre randomised controlled trial (RCT) 10. Similarly, some studies concluded that the additional surgical ablation also decreased the risk of stroke or death and increased early and long-term sinus rhythm maintenance in patients with AF and RMVD 11–13…”
Section: Introductionmentioning
confidence: 99%